The current utility of oligonucleotide aptamers in targeting the MUC1 mucin tumour marker - Flanagan, Shane Patrick (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2018)
Expected release date-April 2020
Keywords: Uncatalogued